(untitled) (World Bulletin of Public Health, 2022)
The article highlights the systems of criteria for the environmental responsibility of young people, which are aimed at the formation of an integrated approach to the organization of environmental education and upbringing. The analysis of the results of the students’ survey is made and it is shown that the axiological, cognitive and activity components in the structure of environmental responsibility are formed differently among students, there are significant differences in the differences in the structure of environmental responsibility between students, which indicates the absence of an integrated approach to environmental education and upbringing